Anti-SARS-CoV-2 monoclonal antibodies for the treatment of active COVID-19 in multiple sclerosis: An observational study. (June 2022) - Manzano, Giovanna S; Rice, Dylan R; Klawiter, Eric C; Matiello, Marcelo; Gillani, Rebecca L; Tauhid, Shahamat S; Bakshi, Rohit; Mateen, Farrah J
Monoclonal antibodies (mAbs) against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) received emergency use authorization for the acute treatment of COVID-19. We are not aware of published data on their use in immunosuppressed people with multiple sclerosis (pwMS). We report 23 pwMS (mean age = 49 years, ocrelizumab ( n  = 19), fingolimod ( n  = 2), vaccinated with at least an initial series ( n  = 19)) who received mAb for acute COVID-19. Following mAb receipt, approximately half recovered in <7 days (48%). There were no adverse events or deaths. Use of mAb for pwMS treated with fingolimod or ocrelizumab was not observed to be harmful and is likely helpful for treatment of acute COVID-19.